Comparison of the Service Areas of Major Universities in Turkey - Sevkiye Sence Turk (European Regional Science Association (ERSA), 1998)
Abstract: Urbanization and an increase in the workforce in many sectors in Turkey has led to an increase in demand for higher education in recent years. To satisfy this demand, the student capacity of existing universities has been increased, while new universities have been founded. This study investigates the influence of three major universities in Turkey in order to evaluate their efficiency and use their results the decision of the location of new universities. Previous studies take into consideration different variables for the locational decisions of the universities, such as, population, employment, educational level, income, educational facilities, e.t.c. In recent years, many studies in the field of educational planning, both national and regional, have also included the location and distribution of facilities of each level of the educational system. Few of these studies are based on analytical research of university locations, however, there have been many analytical studies in the fields of public facility location. Therefore, this study investigates the frequency to the major universities by lacking into consideration, size of the universities, distance to the university, population, employment, educational level, income, students, educational facilities , social facilities of the origine provinces. According to the results, the major universities with English education attract more students from the major cities than the public universities with Turkish education. The results of the study can be used to determine the growth strategies of the universities.
Keywords: 330